Tecnologia wireless: funcionamento e aspectos no mercado - FROIS, Elton Gustavo (004, 2005)
Nesta monografia abordamos a Tecnologia sem fio no geral para entendermos melhor seu funcionamento, aplicações e aspectos que mostrarão como essa tecnologia vem se desenvolvendo e crescendo para alcançar os objetivos que as companhias e o mercado propõe, pois todos esperam ansiosos pela mobilidade total.

In this work we broach the Wireless Technology in general ways and then we'll understand better its functioning, applications and features that it'll show us how this technology have been developed and grown to reach the objectives that the companies and the market to aim to do, because everyone waiting by a total mobility.
Wireless technology: how it works and market aspects
Keywords: Wireless; Tecnologia; Informação e Comunicação